The Effect of Halal Labeling and Product Quality on Muslim Consumer Purchase Decisions on Safi Cosmetic Products with Brand Image as a Mediating Variable - Rahmawati, Asanti Arum; Zakiy, Muhammad (Universitas Muhammadiyah Yogyakarta, 2023)
This study aims to determine the effect of halal labeling and product quality on Muslim consumers' purchasing decisions on Safi cosmetic products mediated by brand image. The current market competition related to cosmetic sales is very high, followed by the presence of many brands that release several products. Producers must have products that have their own charm that can increase consumer buying interest in making purchasing decisions. The sample in this study was Muslim female students in Yogyakarta who had purchased and used Safi products. The number of samples used amounted to 154 respondents. The method used to take samples is purposive sampling. This study uses primary data obtained from distributing online questionnaires via the Google form. The data obtained was analyzed using Smart PLS 3.0. The results of the study show that halal labeling and product quality have a positive effect on brand image. The study results also show that brand image has no effect on purchasing decisions. Brand image does not mediate the relationship between halal labeling and product quality on purchasing decisions. The results of this study can be a reference for Safi companies in improving aspects of halal labeling and product quality so as to create a good brand image for consumers in order to increase purchasing decisions.